FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN KONSUMEN DALAM MEMBELI BERAS HITAM ORGANIK DI TOKO BERAS HASKAMELANG MELALUI TOKOPEDIA - Putri, Gabrella Kezia Efriana; Kusno, Kuswarini (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Technological developments encourage producers to trade online using the internet as a marketplace, one of which is the Haskamelang Rice Store which sells BHO on Tokopedia. The research objectives are 1). describe the characteristics of consumers who buy BHO at Haskamelang Rice Store through Tokopedia and 2). analyze the factors that influence consumer decisions to buy organic black rice. The research design uses a quantitative design with survey techniques. A sample size of 35 was drawn using a simple random sampling technique. Primary data were analyzed using frequency distribution analysis to achieve goal 1 and multiple linear regression analysis to achieve goal 2. The results showed that the R2 value obtained was 0.52, meaning that variations in buying decisions can be explained by variables of ease of use, personal experience, time management, personal nature, service quality, easy payment options, consumer reviews and recommendations and easy accessibility as much as 52% and the remaining 48% is explained by other variables outside the model. The eight variables influence simultaneously but do not partially and significantly affect the purchase decision at the 5% level of significance. In general, the majority of BHO consumers are married women, have a family of 2 dependents in the early elderly age group, domiciled in Jakarta with a bachelor's degree. Working as an entrepreneur with middle to upper income.